2014
DOI: 10.3389/fnhum.2014.00377
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the power of neuroplasticity for intervention

Abstract: A fundamental property of the brain is its capacity to change with a wide variety of experiences, including injury. Although there are spontaneous reparative changes following injury, these changes are rarely sufficient to support significant functional recovery. Research on the basic principles of brain plasticity is leading to new approaches to treating the injured brain. We review factors that affect synaptic organization in the normal brain, evidence of spontaneous neuroplasticity after injury, and the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 106 publications
(118 reference statements)
1
54
0
Order By: Relevance
“…Fourth, it remains unclear whether the SMART program in individuals with chronic TBI led to recovery or compensation of altered neural circuitry that resulted from TBIs. Although improvement in neuropsychological tests performance is observed, “true” recovery of neural circuitry of injured brain following training may be unlikely (Kolb & Muhammad, 2014). Future comparisons with healthy individuals may address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, it remains unclear whether the SMART program in individuals with chronic TBI led to recovery or compensation of altered neural circuitry that resulted from TBIs. Although improvement in neuropsychological tests performance is observed, “true” recovery of neural circuitry of injured brain following training may be unlikely (Kolb & Muhammad, 2014). Future comparisons with healthy individuals may address this question.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in results might also be due to a balance between a drug’s neurotropic and neurotoxic effects. It is intriguing, for example, that treatment with amphetamine has been associated with enhanced neuroplasticity when administered to brain-injured animals in combination with physical therapy (Kolb and Muhammad, 2014). Some of the variation in results is due to method variance.…”
Section: Discussionmentioning
confidence: 99%
“…Improved neural health of damaged structures must rely on neuroplasticity. Animal research provides evidence that behavioral, environmental, pharmacological, and cell-based therapies are correlated with some functional improvement following brain injury (Kolb and Muhammad, 2014). For example, animal studies have shown that exercise may have positive effects on brain structure by increasing neurotrophic factors and elevating the expression of anti-inflammatory cytokines (Svensson et al, 2015).…”
Section: Treatment Implicationsmentioning
confidence: 99%
“…This proposal was highly prescient and was confirmed by imaging and electrophysiological studies almost a century later. [10][11][12] Neuroplasticity involves functional adaptations that occur at various different levels in MS. [13][14][15][16][17] At the cellular level, changes include axonal sprouting (increased arborisation of neurones), changes of synaptic stability and reorganisation of synapses. At the tissue level, there is resorption of oedema and rearrangement of Na-channels on axons beyond the nodes of Ranvier.…”
Section: The Importance Of Neuroplasticity In Multiple Sclerosismentioning
confidence: 99%